THE SECRET MEMORY. HOW THE GONCOURT 2021, MOHAMED MBOUGAR SARR, REWRITES THE STORY OF THE “BLACK RIMBAUD” - ILEA, Laura T. (Studia Universitatis Babeș-Bolyai Philologia, 2024)
The Secret Memory. How the Goncourt 2021, Mohamed Mbougar Sarr, Rewrites the Story of the “Black Rimbaud”. In a mixture of “savage detective story” à la Bolaño, of diary, journalism, interviews and discussions on “plagiarism,” the revolutionary book of Mohamed Mbougar Sarr rewrites the history of Western relations to Africa, to its cultures and its storytelling, but also to different forms of marginality, since its main character, Elimane Madag, is also travelling to South America, being part of its most interesting intellectual circles – through, for instance, Sábato, Gombrowicz, Silvina and Victoria Ocampo. Through voices of Senegalese, Haitian, Argentinian writers and poets, through an apocryphal rewriting of the literary history of the twentieth century, through subverting the theory of plagiarism (since African myths are reinterpreted and melted in the Western culture, similar to African artefacts after the expedition Dakar-Djibouti), as well as through detective journalism (since many characters are interrogating the relation facts-fiction), the marginal and the minor are presented as an alternative, disruptive literary history of the twentieth and of the beginning of the twenty-first century. Memoria secretă. Despre cum laureatul premiului Goncourt 2021, Mohamed Mbougar Sarr, rescrie povestea unui „Rimbaud negru”. Într-un amestec de „detectivism sălbatic” à la Bolaño, de jurnal, jurnalism, interviuri și discuții despre „plagiat”, romanul revoluționar al lui Mohamed Mbougar Sarr rescrie istoria relațiilor Occidentului cu Africa, cu culturile sale și cu modul ei de a povesti, dar și cu forme diferite de marginalitate, din moment ce personajul principal, Elimane Madag, călătorește în egală măsură în America de Sud, făcând parte din cercurile ei intelectuale cele mai interesante – prin intermediul, de exemplu, al lui Sábato, Gombrowicz, Silvina și Victoria Ocampo. Trecând prin voci de scriitori și poeți senegalezi, haitieni și argentinieni, printr-o rescriere apocrifă a istoriei literare a secolului XX, prin subversiunea teoriei plagiatului (din moment ce mituri africane sunt reinterpretate și preluate în cultura occidentală, la fel cu artefactele africane, după expediția Dakar-Djibouti), precum și prin jurnalism detectivist (întrucât multe dintre personaje interoghează relațiile dintre fapte și ficțiune), marginalul și minorul sunt prezentate ca o istorie literară alternativă, perturbatoare a secolului XX și a începutului de secol XXI. Cuvinte-cheie: marginalitate, minor, mituri africane, cultură occidentală, plagiat Article history: Received 26 April 2024; Revised 04 June 2024; Accepted 12 June 2024; Available online 25 June 2024; Available print 30 June 2024.